Student-Centered Learning in Low-Resource Asian ELT Contexts: A Systematic Literature Review of Challenges and Strategies - Sandi Maulana Abdillah; Muhamad Acep Ode; Fazri Nur Yusuf (Journal of English Language Studies, 2025)
This Systematic Literature Review (SLR) analyzes the challenges and strategies involved in implementing Student-Centered Learning (SCL) in low-resource, non-English-speaking Asian contexts within English Language Teaching (ELT). While SCL promotes autonomy, collaboration, and critical thinking, its application in these settings faces major barriers including infrastructure deficiencies, inadequate teacher training, cultural resistance, and institutional constraints. Students often struggle with self-regulation and collaborative learning, while teachers revert to traditional methods due to inadequate preparation, lack of support, and rigid curricula. Student resistance to independent and collaborative tasks also hampers its adoption. To address these issues, this study identifies key strategies such as enhancing teacher training, optimizing resources, reforming policies, gradually integrating SCL, and leveraging mobile learning tools. Findings indicate that context-sensitive adaptations, professional development programs, and institutional support are critical for sustainable SCL implementation. The study highlights the need for curriculum flexibility, alternative assessments, and collaborative teacher networks to overcome existing barriers. Future research should investigate longitudinal impacts of SCL and scalable solutions for resource-constrained ELT settings. These insights provide practical recommendations for educators, policymakers, and curriculum designers aiming to foster meaningful student engagement in challenging learning environments.